Neuromuscular Electrical Stimulation Reduces Leg Cramps in Patients With Lumbar Degenerative Disorders: A Randomized Placebo‐Controlled Trial. Issue 8 (9th November 2020) - Harmsen, Jan‐Frieder; Sistig, Anna; Fasse, Alessandro; Hackl, Michael; Wegmann, Kilian; Behringer, Michael
Abstract: Objectives: Lumbar spinal stenosis (LSS) and lumbar disc herniation (LDH) are often accompanied by frequently occurring leg cramps severely affecting patients' life and sleep quality. Recent evidence suggests that neuromuscular electric stimulation (NMES) of cramp‐prone muscles may prevent cramps in lumbar disorders. Materials and Methods: Thirty‐two men and women (63 ± 9 years) with LSS and/or LDH suffering from cramps were randomly allocated to four different groups. Unilateral stimulation of the gastrocnemius was applied twice a week over four weeks (3 × 6 × 5 sec stimulation trains at 30 Hz above the individual cramp threshold frequency [CTF]). Three groups received either 85%, 55%, or 25% of their maximum tolerated stimulation intensity, whereas one group only received pseudo‐stimulation. Results: The number of reported leg cramps decreased in the 25% (25 ± 14 to 7 ± 4; p = 0.002), 55% (24 ± 10 to 10 ± 11; p = 0.014) and 85%NMES (23 ± 17 to 1 ± 1; p < 0.001) group, whereas it remained unchanged after pseudo‐stimulation (20 ± 32 to 19 ± 33; p > 0.999). In the 25% and 85%NMES group, this improvement was accompanied by an increased CTF ( p < 0.001). Conclusion: Regularly applied NMES of the calf muscles reduces leg cramps in patients with LSS/LDH even at low stimulation intensity.